Solid waste-based 3d printing mortar
Patent Information
- Application Number
- CN202611110787.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-24
- Publication Date
- 2026-10-27
AI Technical Summary
[0005]针对现有技术的不足,本发明提供了一种固废基3D打印砂浆,旨在解决现有技术中3D打印建筑材料高度依赖高碳排硅酸盐水泥与天然砂、在高固废替代率下打印构件早期承载力弱且易开裂,以及再生建筑骨料预湿工艺引发的实际用水量失准与浆体流变性能不稳定的问题
[0030]1、本发明通过以矿粉、粉煤灰、工业副产氟石膏及碱性激发固废组成的多源复合体系替代大部分传统硅酸盐水泥,并配合使用建筑垃圾破碎干骨料作为实体骨料来源。这种配伍结构在降低材料制备体系总体碳排放与能源消耗的同时,减轻了对天然河砂资源的依赖,在满足3D打印连续挤出要求的基础上实现了工业及建筑废弃物的高比例转化,有利于控制整体建筑打印材料的制备成本。
Smart Images

Figure CN122977809A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of interdisciplinary technology of building materials and additive manufacturing, specifically a solid waste-based 3D printing mortar. Background Technology
[0002] Existing extrusion-based 3D printed building materials primarily rely on high doses of ordinary silicate cement as the core cementitious system, typically combined with natural river sand or manufactured sand as basic aggregates. This batching system results in high carbon emissions and energy consumption throughout the material preparation cycle, and its manufacturing costs are highly susceptible to the increasing scarcity of natural sand and gravel resources and restrictions on their extraction. Although the industry has attempted to introduce some industrial solid waste such as slag or fly ash to reduce cement usage, the actual blending ratio of these solid wastes in current conventional engineering applications is low, making it difficult to substantially achieve the high-value-added conversion of large quantities of solid waste and the large-scale carbon reduction engineering goals.
[0003] When attempting to significantly increase the substitution rate of industrial solid waste in formulations, a technical bottleneck arises where it is difficult to simultaneously achieve early strength development and extrusion rheology. Due to the reduced proportion of conventional silicate cement, the alkali-activated driving force within the system weakens, resulting in a relatively slow reaction process for potentially hydrating active materials. This reaction lag weakens the initial load-bearing capacity of the slurry after detaching from the printing nozzle, making it prone to interlayer collapse or localized deformation during component stacking. Simultaneously, in low-cement-content formulations, the industrial by-product gypsum introduced to activate the material carries a high risk of micro-expansion, easily inducing internal stress concentration during hydration, thus leading to varying degrees of cracking on the surface of the printed components.
[0004] Furthermore, in attempts to utilize waste construction materials to prepare recycled aggregates as a substitute for natural sand, conventional preparation processes necessitate pre-soaking or pre-wetting of the aggregates due to their high capillary porosity and water absorption characteristics. This is to prevent the aggregates from rapidly absorbing free water from the mixture during the initial mixing stage, which could lead to false setting of the slurry. However, because different batches of recycled aggregates have varying initial states and water absorption rates, it is difficult to accurately control the pre-wetting moisture content of the aggregates on-site. This error in moisture control directly causes the actual water consumption during slurry preparation to deviate from the theoretical design value, thereby severely interfering with the sensitive rheological parameters of 3D printing mortar and causing fluctuations in continuous extrusion stability and the mechanical properties of the finished product. Summary of the Invention
[0005] To address the shortcomings of existing technologies, this invention provides a solid waste-based 3D printing mortar, aiming to solve the problems of existing 3D printing building materials being highly dependent on high-carbon silicate cement and natural sand, having weak early load-bearing capacity and being prone to cracking under high solid waste substitution rates, and the inaccuracy of actual water consumption and unstable mortar rheological properties caused by the pre-wetting process of recycled building aggregates.
[0006] To achieve the above objectives, the present invention provides a solid waste-based 3D printing mortar, which employs the following technical solution:
[0007] A solid waste-based 3D printing mortar is made from the following raw materials in parts by weight:
[0008] Mineral powder 42-60 parts; fly ash 15-30 parts; industrial by-product fluorogypsum 16-20 parts; rapid-hardening sulfoaluminate cement 3-10 parts; alkaline activated solid waste 2-6 parts; crushed dry aggregate from construction waste 80-120 parts; polycarboxylate-based high-performance water-reducing agent powder 0.15-0.35 parts; water-retaining thickener 0.005-0.03 parts; microfiber 0.03-0.12 parts; water 18-28 parts;
[0009] The mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, and alkaline activated solid waste together constitute the cementitious material, and the total weight of the cementitious material is 100 parts.
[0010] By adopting the above technical solution, since a multi-source solid waste composite cementing system is used to replace most of the traditional silicate cement, and under the rheological regulation of polycarboxylate-based high-performance water-reducing agent powder and water-retaining thickener, it is possible to obtain relatively stable early strength development while reducing the cost of the material system, thereby meeting the basic requirements for continuous stacking of 3D printed components.
[0011] The synergistic hydration reaction mechanism of the above-mentioned basic formula is mainly reflected in the following process: In the initial stage of water mixing, the fast-hardening sulfoaluminate cement in the system usually undergoes preferential hydration to generate ettringite and alumina gel, which provides a foundation for the initial bearing of the printing bottom layer.
[0012] Subsequently, as the alkaline-activated solid waste dissolves in the aqueous phase, the released hydroxide ions cause the alkalinity of the liquid phase to rise. Under this highly alkaline environment, the dense glassy structure on the surface of mineral powder and fly ash is excited and depolymerizes, leading to the breakage of internal Si-O-Si and Al-O-Al bonds, thereby releasing reactive silicon-oxygen tetrahedra and aluminum-oxygen tetrahedra.
[0013] Meanwhile, the dissolved industrial byproduct fluorogypsum replenishes the sulfate ions required by the system. These ions undergo secondary reactions with the previously released active aluminum phase and liquid-phase free calcium ions, continuously generating needle-like columnar ettringite crystals; simultaneously, the active silica phase undergoes condensation to produce hydrated calcium silicate gel. The generated gel products and crystals interweave, gradually filling the gradation pores of the crushed dry aggregate of construction waste, thereby constructing a relatively dense hardened network.
[0014] Preferably, the mineral powder is of grade S95, and the specific surface area of the mineral powder is 400-450 m². 2 / kg; the fly ash is Class F, Grade II fly ash; the free moisture content of the industrial by-product fluorogypsum is ≤1.5%. The pH of the alkaline activated solid waste is ≥12.5, and the alkaline activated solid waste is calcium carbide slag powder or steel slag powder.
[0015] By adopting the above technical solutions, the alkalinity of calcium carbide slag powder or steel slag powder itself can maintain the activation environment of the system to a certain extent. Compared with the direct addition of strong alkaline reagents such as sodium hydroxide, it helps to reduce the efflorescence phenomenon that may occur in the later stage of the components. In addition, the control of the free water content of industrial by-product fluorogypsum is conducive to the uniform dispersion of various powder particles in the dry mixing stage.
[0016] Preferably, the crushed dry aggregate of construction waste is composed of waste concrete and waste bricks and tiles that have been crushed by jaw crushers and impact crushers, and then collected by screening through an iron mesh screen with a diameter of 3mm, resulting in particles with a particle size of ≤3mm, and naturally air-dried to a free moisture content of ≤1.5%.
[0017] By adopting the above technical solution, waste concrete and waste bricks and tiles are processed into recycled aggregates for utilization. Because waste bricks and tiles themselves have high capillary porosity and rough, porous surfaces, they possess a strong water absorption and retention capacity. This keeps their free moisture content in a dry state, forming the physical prerequisite for subsequent control of the overall rheological properties of the mixture.
[0018] Preferably, the water-retaining and thickening agent is hydroxypropyl methylcellulose or microbial polysaccharide sorbate. The microfibers are selected from alkali-resistant glass fibers, polypropylene fibers, or basalt fibers, and the length of the microfibers is 3-6 mm.
[0019] By adopting the above technical solution, the long polymer chains of the water-retaining thickener intertwine in the liquid phase to form a spatial network structure, which can appropriately increase the yield stress of the slurry and slow down the physical sedimentation process of the particles; the microfibers are distributed in three-dimensional random direction inside the mortar matrix, and with their bridging effect, they can limit the initiation and further expansion of microcracks in the extrusion molding and plastic shrinkage stages to a certain extent.
[0020] Preferably, the method for preparing the solid waste-based 3D printing mortar includes the following steps:
[0021] Weigh out the following components by weight: mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, alkaline activated solid waste, crushed dry aggregate from construction waste, polycarboxylate-based high-performance water-reducing agent powder, water-retaining thickener, microfiber, and water.
[0022] The weighed mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, alkaline activated solid waste, water-retaining thickener, and microfiber are all added to a twin-shaft forced mixer and mixed in a dry environment for 11 minutes.
[0023] A portion of the total water volume is measured and mixed with the polycarboxylate-based high-performance water-reducing agent powder. The mixture is then added to the twin-shaft forced mixer for stirring to prepare a reference slurry phase. The measured portion of water accounts for 50%-70% of the total weight of water. After adding the measured portion of water and the polycarboxylate-based high-performance water-reducing agent powder, the mixture is first stirred at low speed for 30 seconds, and then switched to high-speed forced stirring for 1.5 minutes.
[0024] Keep the twin-shaft forced mixer running, pour the dry aggregate of the construction waste in a dry state directly into the reference slurry phase, and then add the remaining water, continue to stir, and finally discharge the solid waste-based 3D printing mortar mixture.
[0025] Specifically, it is strictly prohibited to pre-wet or spray the crushed dry aggregate of construction waste; the remaining water added accounts for 30%-50% of the total weight of water; after adding the dry crushed dry aggregate of construction waste and the remaining water, the mixture is continuously and forcibly stirred at high speed for 2.5 minutes.
[0026] By adopting the above technical solution, the stepwise pulping and aggregate retardation coating mixing process can improve the balance between mortar pumping leveling and extrusion molding from a physical rheological perspective.
[0027] During the initial mixing of the slurry, some of the liquid water comes into contact with the water-reducing agent powder. The main chain of the water-reducing agent molecules adsorbs onto the surface of the cementitious material, and the fine powder particles deflocculate due to the steric hindrance effect of the side chains. At this time, since the porous dry aggregate of construction waste has not yet been added, the system has relatively abundant free water. Forced stirring can form a reference slurry phase with low apparent viscosity and good pumpability.
[0028] When dry aggregate from construction waste and residual water are added to the system, the negative pressure gradient generated between the capillaries inside the dry aggregate and the surrounding liquid phase causes it to quickly absorb some of the free water from the reference slurry phase. This interphase water transfer leads to a reduction in the interparticle spacing within the mortar, increasing the number of solid-phase contact points, which macroscopically manifests as an increase in the system's physical frictional resistance. Based on this process, after the mixture is transported through pipelines and exits the printing nozzle, its static yield stress will experience a significant jump, causing the slurry to transform from a fluid state to a plastic body with preliminary support capabilities. This better resists the self-weight load applied by the upper continuous printing strips, reducing the risk of early collapse of the component or deformation of the underlying layer.
[0029] This invention provides a solid waste-based 3D printing mortar. It has the following beneficial effects:
[0030] 1. This invention replaces most of the traditional silicate cement with a multi-source composite system composed of mineral powder, fly ash, industrial by-product fluorogypsum, and alkaline activated solid waste, and uses crushed dry aggregate from construction waste as a source of solid aggregate. This formulation reduces the overall carbon emissions and energy consumption of the material preparation system while lessening the dependence on natural river sand resources. It achieves a high proportion of conversion of industrial and construction waste while meeting the continuous extrusion requirements of 3D printing, which is beneficial for controlling the overall preparation cost of building printing materials.
[0031] 2. The preparation method designed in this invention relies on a step-by-step high-shear slurry preparation and aggregate hysteresis coating process, allowing crushed and screened construction waste to be directly fed into the mixing equipment in a naturally dried state, eliminating the pre-wetting or spraying steps required in conventional operations. This not only reduces the risk of batch quality fluctuations caused by the difficulty in accurately controlling the moisture content in traditional recycled aggregate pretreatment processes, but also utilizes the capillary water absorption mechanism of dry aggregate in the later stages of mixing to promote a rapid increase in the static yield stress of the slurry during the extrusion molding stage, thereby improving the load-bearing and shape-preserving capacity of the bottom layer of the printed component.
[0032] 3. The industrial by-product fluorogypsum added to the system can undergo a secondary reaction with the active aluminum phase of rapid-hardening sulfoaluminate cement. The continuously generated ettringite crystals can, to some extent, compensate for the early plastic shrinkage of the slurry. Combined with the random distribution of microfibers within the mortar matrix, the multi-component synergistic dispersion of capillary shrinkage stress during the slurry setting stage helps limit the initiation and propagation of microcracks on the component surface, thereby maintaining the overall structural continuity of the 3D printed solid building components. Attached Figure Description
[0033] Figure 1 The X-ray diffraction of Example 1, Comparative Example 1, and Comparative Example 2 after 28 days of curing is shown. Detailed Implementation
[0034] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0035] Examples 1-3:
[0036] Example 1:
[0037] This embodiment provides a method for preparing solid waste-based 3D printing mortar, including the following steps:
[0038] (1) Material preparation and weighing: Weigh a total of 100 kg of cementitious materials, including:
[0039] Mineral powder (S95 grade, specific surface area 400-450m²) 2 53 kg of fly ash (Class F, Grade II), 18 kg of industrial by-product fluorogypsum (free moisture content ≤1.5%), 20 kg of rapid-hardening sulfoaluminate cement, and 4 kg of calcium carbide slag powder (pH ≥12.5).
[0040] Aggregate preparation and weighing: After crushing the construction waste (waste concrete and waste bricks and tiles) with a jaw crusher and an impact crusher, the particles with a diameter ≤3mm are collected by screening through a 3mm wire mesh and air-dried naturally until the free moisture content is ≤1.5%. Weigh 100kg of the crushed dry aggregate from the above construction waste, and any pre-wetting or spraying treatment is strictly prohibited.
[0041] Weigh the following additives: 0.20 kg of polycarboxylate-based high-performance water-reducing agent powder, 0.015 kg of water-retaining thickener (hydroxypropyl methylcellulose, HPMC), and 0.08 kg of microfiber (alkali-resistant glass fiber, 6 mm in length).
[0042] Calculation of total water consumption: Based on a water-to-binder ratio of 0.25, the total water consumption is 25 kg.
[0043] (2) Dry powder premixing: The above-weighed mineral powder, fly ash, fluorogypsum, rapid hardening sulfoaluminate cement, carbide slag powder, water-retaining thickener and alkali-resistant glass fiber are put into a twin-shaft forced mixer and mixed for 11 minutes in a dry environment so that the powder materials and microfibers are evenly dispersed on a macroscopic scale.
[0044] (3) Stepwise high-shear slurry preparation (first water addition stage): Measure 15 kg of water (60% of the total water volume) into the 25 kg total water volume, mix it with all 0.20 kg of polycarboxylate-based high-performance water-reducing agent powder, and then add it to the above-mentioned twin-shaft forced mixer. First, stir at low speed for 30 seconds, and then switch to high-speed forced stirring for 1.5 minutes. Utilize the strong dispersing effect of the water-reducing agent and the network-forming effect of the water-retaining thickener to obtain a polymer rheological reference slurry phase.
[0045] (4) Aggregate hysteresis encapsulation (second water addition stage): Keep the twin-shaft forced mixer running, and directly pour 100 kg of dry crushed construction waste aggregate into the above-mentioned reference slurry phase, and then immediately add the remaining 10 kg of water (accounting for 40% of the total water volume). Continue high-speed forced mixing for 2.5 minutes, and finally discharge a uniform all-solid waste-based 3D printing mortar mixture.
[0046] Example 2:
[0047] This embodiment provides a method for preparing solid waste-based 3D printing mortar, including the following steps:
[0048] (1) Material preparation and weighing: Weigh a total of 100 kg of cementitious materials, including:
[0049] Mineral powder (S95 grade, specific surface area 400-450m²) 2 / kg) 42kg, fly ash (F class II grade) 30kg, industrial by-product fluorogypsum (free moisture content ≤1.5%) 16kg, rapid hardening sulfoaluminate cement 10kg, carbide slag powder (pH≥12.5) 2kg.
[0050] Aggregate preparation and weighing: After crushing the construction waste (waste concrete and waste bricks and tiles) with a jaw crusher and an impact crusher, the particles with a diameter ≤3mm are collected by screening through a 3mm wire mesh and air-dried naturally until the free moisture content is ≤1.5%. Weigh 120kg of the crushed dry aggregate from the above construction waste, and any pre-wetting or spraying treatment is strictly prohibited.
[0051] Weigh the following additives: 0.35 kg of polycarboxylate-based high-performance water-reducing agent powder, 0.03 kg of water-retaining thickener (hydroxypropyl methylcellulose, HPMC), and 0.12 kg of microfiber (polypropylene fiber, 3 mm in length).
[0052] Calculation of total water consumption: Based on a water-to-binder ratio of 0.28, the total water consumption is 28 kg.
[0053] (2) Dry powder premixing: The above-weighed mineral powder, fly ash, fluorogypsum, rapid hardening sulfoaluminate cement, carbide slag powder, water-retaining thickener and polypropylene fiber are put into a twin-shaft forced mixer and mixed for 11 minutes in a dry environment so that the powder materials and microfibers are evenly dispersed on a macroscopic scale.
[0054] (3) Stepwise high-shear slurry preparation (first water addition stage): Measure 19.6 kg of water (70% of the total water volume) into the total water volume of 28 kg, mix it with all 0.35 kg of polycarboxylate-based high-performance water-reducing agent powder, and then add it to the above-mentioned twin-shaft forced mixer. First, stir at low speed for 30 seconds, and then switch to high-speed forced stirring for 1.5 minutes. Utilize the strong dispersing effect of the water-reducing agent and the network-forming effect of the water-retaining thickener to prepare a polymer rheological reference slurry phase.
[0055] (4) Aggregate hysteresis coating (second water addition stage): Keep the twin-shaft forced mixer running, and directly pour 120 kg of dry crushed construction waste aggregate into the above-mentioned reference slurry phase, and then immediately add the remaining 8.4 kg of water (accounting for 30% of the total water volume). Continue high-speed forced mixing for 2.5 minutes, and finally discharge a uniform all-solid waste-based 3D printing mortar mixture.
[0056] Example 3:
[0057] This embodiment provides a method for preparing solid waste-based 3D printing mortar, including the following steps:
[0058] (1) Material preparation and weighing: Weigh a total of 100 kg of cementitious materials, including:
[0059] Mineral powder (S95 grade, specific surface area 400-450m²) 2 60kg of fly ash (Class F, Grade II), 15kg of industrial by-product fluorogypsum (free moisture content ≤1.5%), 16kg of rapid-hardening sulfoaluminate cement, and 6kg of steel slag powder (as alkaline activated solid waste, pH ≥12.5).
[0060] Aggregate preparation and weighing: After crushing the construction waste (waste concrete and waste bricks and tiles) with jaw crushers and impact crushers, the particles with a diameter ≤3mm are collected by screening through a 3mm wire mesh and air-dried naturally until the free moisture content is ≤1.5%. Weigh 80kg of the crushed dry aggregate from the above construction waste, and any pre-wetting or spraying treatment is strictly prohibited.
[0061] The following additives are weighed: 0.15 kg of polycarboxylate-based high-performance water-reducing agent powder, 0.005 kg of water-retaining thickener (microbial polysaccharide warm wheel glue), and 0.03 kg of microfiber (basalt fiber, 6 mm in length).
[0062] Calculation of total water consumption: Based on a water-cement ratio of 0.18 (for constructing an extremely dry and thick system), the total water consumption is 18 kg.
[0063] (2) Dry powder premixing: The above-weighed mineral powder, fly ash, fluorogypsum, rapid hardening sulfoaluminate cement, steel slag powder, water-retaining thickener and basalt fiber are put into a twin-shaft forced mixer and mixed for 11 minutes in a dry environment so that the powder materials and microfibers are evenly dispersed on a macroscopic scale.
[0064] (3) Stepwise high-shear pulping (first water addition stage): Measure 9 kg of water (50% of the total water volume) into the total water volume of 18 kg, mix it with all 0.15 kg of polycarboxylate-based high-performance water-reducing agent powder, and then add it to the above-mentioned twin-shaft forced mixer. First, stir at low speed for 30 seconds, and then switch to high-speed forced stirring for 1.5 minutes. Use mechanical shear force to break up flocculation under low water-binder ratio, and at the same time, rely on the network-forming effect of water-retaining thickener to obtain a polymer rheological reference slurry phase.
[0065] (4) Aggregate hysteresis encapsulation (second water addition stage): Keep the twin-shaft forced mixer running, and directly pour 80 kg of dry crushed construction waste aggregate into the above-mentioned reference slurry phase, and then immediately add the remaining 9 kg of water (accounting for 50% of the total water volume). Continue high-speed forced mixing for 2.5 minutes, and finally discharge a highly thixotropic all-solid waste-based 3D printing mortar mixture.
[0066] Comparative Examples 1-5:
[0067] Comparative Example 1:
[0068] Compared with Example 1, the difference is that no industrial by-product fluorogypsum and rapid-hardening sulfoaluminate cement were added to the cementitious material, and the missing mass fraction (a total of 25 kg) was replaced by an equal amount of mineral powder, while the rest were the same.
[0069] Comparative Example 2:
[0070] Compared with Example 1, the difference is that no calcium carbide slag powder (alkaline activated solid waste) was added to the cementitious material, and its missing mass share (a total of 4 kg) was replaced by an equal amount of mineral powder, while the rest are the same.
[0071] Comparative Example 3:
[0072] Compared to Example 1, the difference lies in that the preparation process does not employ the stepwise high-shear pulping and aggregate retardation coating process, but instead uses a one-time feeding and mixing method. Specifically, all powder materials, dry aggregates from construction waste, and microfibers are added to the mixer at once, followed by all water and water-reducing agent, and then directly forced mixing for 4.5 minutes. The proportions of the remaining materials remain the same.
[0073] Comparative Example 4:
[0074] The difference from Example 1 is that no water-retaining thickener (hydroxypropyl methylcellulose, HPMC) was added to the additives; all other aspects are the same.
[0075] Comparative Example 5:
[0076] Compared with Example 1, the difference is that a traditional 3D printing mortar system is used, that is, all the cementitious materials are replaced with ordinary silicate cement (100kg in total), all the aggregates are replaced with natural river sand (100kg in total), and no carbide slag, fluorogypsum and water-retaining thickener are added. Other aspects such as the amount of water-reducing agent and the water-cement ratio are the same.
[0077] Test Example 1:
[0078] Test steps:
[0079] 1) Collect the mortar mixtures after mixing in Examples 1, 2, 3 and Comparative Example 4.
[0080] 2) Load the quantitative mixture into the test container of the coaxial cylindrical rheometer and set the test temperature to 20℃. Start the pre-shear program to eliminate data bias caused by sample loading history. Control the shear rate from 0.1 s⁻¹. -1 Increase the speed uniformly to 100s -1 Then from 100s -1 Decrease at a constant speed to 0.1s -1 Record the corresponding shear stress data.
[0081] 3) Generate upward and downward data columns based on the data output by the rheometer, plot the thixotropic ring curve, calculate the area enclosed by the two curves, and extract the static yield stress and plastic viscosity index.
[0082] 4) Load the mortar from the same batch after the rheological test into the hopper of the single-screw 3D printer and start the continuous extrusion program.
[0083] 5) Connect a pressure sensor to the end of the delivery hose near the printing nozzle. Set the sampling frequency to 1Hz and continuously record the pressure change data inside the hose within 20 minutes after extrusion starts, recording whether extrusion is interrupted and the corresponding time point.
[0084] Test data:
[0085] Table 1. Monitoring data of mortar rheological parameters and pumping pressure
[0086] Test object Static yield stress (Pa) Plastic viscosity (Pa·s) Thixotropic ring area (Pa / s) Average pressure over 20 minutes (MPa) Maximum pressure fluctuation difference (MPa) Downtime due to pipe blockage (min) Example 1 1542.4 32.7 28540 1.45 0.12 - Example 2 1215.8 28.1 22105 1.31 0.09 - Example 3 1876.2 45.4 34512 1.76 0.18 - Comparative Example 4 850.5 15.2 8420 / / 6.4
[0087] Note: "-" in the table indicates that no pipe blockage or shutdown occurred during the 20-minute test period; " / " indicates that the complete 20-minute statistical data could not be obtained due to premature triggering of the shutdown protection.
[0088] Test conclusion:
[0089] Based on the rheological parameters recorded in Table 1, the slurry mixtures of Examples 1 to 3 exhibit rheological characteristics suitable for continuous extrusion processes in 3D printing. Test data shows that the thixotropic ring area of the above examples ranges from 22105 to 34512 Pa / s. This key indicator physically characterizes the structural reconstruction hysteresis effect of the slurry during shear failure and subsequent shear release, indicating that it possesses excellent thixotropic recovery potential after exiting the printing nozzle. In contrast, Comparative Example 4, without the addition of a water-retaining thickener, shows a drop in static yield stress to 850.5 Pa, and a significant reduction in thixotropic ring area to 8420 Pa / s. This decrease in rheological parameters macroscopically manifests as a weakening ability of the mixture to resist its own weight after extrusion molding, making it more difficult to maintain the initial stacking morphology of the bottom layer of the component.
[0090] Under continuous pumping and extrusion conditions, Examples 1 to 3 exhibited good operational stability within a 20-minute test cycle. Table 1 shows that the maximum difference in pipeline pressure fluctuation for this group of examples was controlled within a narrow range of 0.09 to 0.18 MPa, indicating that the mortar did not encounter an abnormal surge in frictional resistance during screw propulsion and pipeline transportation. Analysis of its internal rheological mechanism reveals that the high-molecular-weight long chains of the water-retaining thickener, combined with the aforementioned stepwise slurry-making process, promote the formation of a viscous physical coating layer on the surface of the dry aggregate from construction waste by the fine powder reference slurry. Under the action of the pumping pressure field, this coating layer effectively delays the rapid reverse permeation of liquid free water into the interior of the dry porous aggregate, thereby maintaining the relative continuity of the lubricating medium between particles and reducing the probability of pressure bleeding.
[0091] In contrast, Comparative Example 4, lacking a water-retaining and thickening system, showed that under continuous screw extrusion, free water in the slurry rapidly seeped into the pores of the highly absorbent dry aggregate from construction waste, leading to a sharp loss of liquid medium in certain sections of the pipeline. This rapid transfer of water between phases directly caused the mixture to dry out and the physical frictional resistance between solid particles to increase sharply. This was reflected in the test data as the inability to obtain a complete 20-minute statistical average, and the equipment shutdown protection being triggered by pump overload after only 6.4 minutes of pipeline operation. In summary, the above comparative tests indicate that the introduction of a water-retaining and thickening agent and the synergistic effect of the delayed coating process on dry aggregate play a supporting role in suppressing the rapid water absorption of high-porosity solid waste aggregate under pressure and ensuring the continuous pumpability of mortar materials.
[0092] Test Example 2:
[0093] Test steps:
[0094] 1) According to the types and amounts of cementitious materials and additives and the corresponding water-cement ratios given in Examples 1 to 3 and Comparative Example 1, the raw materials were weighed and mixed with water to prepare four groups of slurry samples without aggregates for isothermal hydration exothermic tests.
[0095] 2) Seal four groups of quantitative slurry samples in ampoules respectively, and place them in the test channel of an isothermal microcalorimeter. Set the constant temperature environment of the instrument to 20°C, start data acquisition, and continuously monitor the change of heat flow rate within 0 to 12 hours.
[0096] 3) Prepare aggregate-containing mortar mixtures according to the complete proportions and procedures of Examples 1 to 3 and Comparative Example 1, and fill them into the truncated conical die matched with a Vicat apparatus. In an environment of 20°C and 90% relative humidity, periodically measure the sinking depth of the test needle to obtain data on initial setting time and final setting time. The setting time is a time parameter for the mixture to form a structure in a static state after being loaded into the die.
[0097] 4) Load the mortar mixture prepared in the same batch into the storage device of a single-screw 3D printing equipment, set the moving speed of the printing nozzle to 100 mm / s, the single-layer extrusion width to 30 mm, and the single-layer height to 10 mm. Control the equipment to perform continuous vertical surface stacking printing according to a rectangular path with a length and width of 500 mm.
[0098] 5) During the stacking printing process, observe the compressed state of the bottommost layer and the several bottom layers of the component. When it is observed that outward convex deformation occurs on the side of the bottom layer or the overall structure collapses, stop the printing command and record the maximum number of non-deformable stacked layers that have been completed currently.
[0099] Test data:
[0100] Table 2. Data of mortar setting time, stacking printing and thermodynamic parameters
[0101] Test object Initial setting time (min) Final setting time (min) Maximum number of non-variable stacking layers (layers) Time of first exothermic peak (h) Peak heat flux (mW / g) Example 1 24 38 42 0.85 32.4 Example 2 31 45 35 1.15 27.6 Example 3 19 32 48 0.62 38.1 Comparative Example 1 215 284 4 - -
[0102] Note: The "-" in the table means that no identifiable early hydration exothermic peak characteristics were monitored within the test period of 0 to 12 hours, so the occurrence time of the first exothermic peak and the peak heat flow rate were not extracted.
[0103] Test conclusion:
[0104] According to the setting and thermodynamic parameters listed in Table 2, the mortar mixtures of Examples 1 to 3 exhibit early curing characteristics that can well match the continuous 3D printing operation cycle. Thermodynamic monitoring data show that the above examples induce hydration exothermic behavior within the first two hours after mixing with water, the occurrence time of their first exothermic peak is concentrated in the range of 0.62 to 1.15 hours, and the corresponding peak heat flow rate reaches 27.6 to 38.1 mW / g.
[0105] This early surge in heat flow rate primarily stems from the synergistic reaction between industrial by-product fluorogypsum and rapid-hardening sulfoaluminate cement in the formulation. The sulfate ions released as fluorogypsum dissolves in the aqueous phase promote the rapid formation and interlocking of numerous needle-like ettringite crystals in the liquid phase. This crystallization process not only consumes some of the free water within the system but also causes a gradient increase in the internal friction of the mixture, thereby establishing an initial static yield stress to resist deformation under its own weight. Reflected in macroscopic physical indicators, the initial setting times of Examples 1 to 3 were controlled within 19 to 31 minutes, and the final setting state was achieved within 32 to 45 minutes. Although this rapid structure-building mechanism manifests as a shortened setting time under static testing conditions, in actual pumping and extrusion processes, thanks to the continuous dynamic shearing action applied by the screw and the inner wall of the pipeline, the early flocculation network of the mixture is moderately broken, thus maintaining relatively smooth in-pipe transportability.
[0106] Once the mortar material detaches from the printing nozzle and the external dynamic shearing is released, the system can quickly reconstruct its internal support structure based on the previously generated crystal framework. It is precisely this response process, switching from dynamic rheology to static curing, that allows the extruded continuous strips to acquire sufficient physical strength to bear the self-weight load of the upper layers, thus achieving 35 to 48 layers of continuous, non-deformable construction in facade stacking tests. It is worth noting that in Example 3, under the condition of relatively low rapid-hardening sulfoaluminate cement content, the use of a lower water-cement ratio combined with a high amount of mineral powder and the construction of an alkaline activation environment using steel slag powder resulted in a higher concentration of liquid-phase ions and particle contact density within the system. This accelerated the early structural bonding process to some extent, leading to an earlier exothermic peak appearance and a relatively better maximum number of non-deformable stacking layers in the tests.
[0107] In contrast, Comparative Example 1, which lacked the fluorogypsum and rapid-hardening sulfoaluminate cement components, failed to capture an identifiable early hydration exothermic peak during the 0-12 hour isothermal calorimetric monitoring period, indicating a lack of a core driving force for activating early strength within its system. As a result, the initial setting time of this mixture was significantly delayed to 215 minutes, remaining in a plastic flow state lacking sufficient yield stress for an extended period. During continuous printing tests, the extruded bottom layer of mortar failed to establish a structural network to resist the pressure of gravity above, leading to severe outward deformation of the bottom layer only up to the fourth layer, thus triggering the shutdown boundary condition.
[0108] Test Example 3:
[0109] Test steps:
[0110] 1) Mortar mixtures were prepared according to the mix proportions given in Examples 1, 2, 3, Comparative Example 1, and Comparative Example 2. The mixtures were poured into standardized triple molds (40mm × 40mm × 160mm) for molding. The mixtures were cured in a curing chamber at 20°C and 90% relative humidity for 28 days to obtain test blocks.
[0111] 2) Place the test blocks that have been cured for 28 days on a pressure testing machine and test their compressive and flexural strengths according to the cement mortar strength test method. Record the ultimate load when the test block fails under pressure and calculate the corresponding strength values.
[0112] 3) Collect the uncarbonized fragments of the interior of the test blocks of Example 1, Comparative Example 1 and Comparative Example 2 after they were destroyed, and soak them in anhydrous ethanol for 24 hours to terminate the residual hydration reaction.
[0113] 4) Place the soaked fragments in a vacuum drying oven and dry them at 60°C until the mass is constant. Grind the dried fragments into powder using an agate mortar and pestle, and then pass the powder through a 200-mesh square-hole sieve to obtain a powder test sample.
[0114] 5) The powder sample was scanned using an X-ray diffractometer. A copper target Kα radiation source was set with a tube voltage of 40 kV and a tube current of 40 mA. The scanning angle 2θ was set to range from 5° to 40°, with a scanning step size of 0.02°, and diffraction intensity data were collected at the corresponding angles.
[0115] Test data:
[0116] Table 3. Mechanical strength and phase analysis data of mortar at 28 days
[0117] Test object 28-day compressive strength (MPa) 28-day flexural strength (MPa) Relative intensity (cps) of the 9.1° diffraction peak Integral value of the diffraction bag area from 29° to 32° (au) Example 1 42.6 7.8 415 874 Example 2 38.2 6.9 362 751 Example 3 46.1 8.4 486 925 Comparative Example 1 31.4 5.6 28 702 Comparative Example 2 12.5 2.1 374 -
[0118] Note: The “-” in the table indicates that the curve shape tends to be flat within the target diffraction angle range, and no identifiable broadened diffraction bag is formed. Therefore, the area integral data of the corresponding range is not extracted.
[0119] Test conclusion:
[0120] Based on the data extracted from Table 3, the compressive strength of Examples 1 to 3 at 28 days of age ranged from 38.2 to 46.1 MPa, and the flexural strength ranged from 6.9 to 8.4 MPa. This strength level has the potential to meet the load-bearing design requirements of the component foundation. Combined with... Figure 1 Further analysis was conducted on the phase states of hydration products inside the cured specimens. This analysis aimed to visually reflect the influence of early sulfate reaction components and alkaline activating components on the formation pathways of hydration products. Figure 1XRD comparisons were performed on Example 1, Comparative Example 1, and Comparative Example 2. In the figure, the horizontal axis represents the diffraction angle 2θ, and the vertical axis represents the recorded diffraction intensity signal; the solid line represents Example 1, the dashed line represents Comparative Example 1, and the dotted line represents Comparative Example 2. The curves in each group were shifted along the vertical axis to facilitate feature comparison.
[0121] Observing the solid line trend of Example 1, obvious crystallization diffraction characteristic peaks are present near diffraction angles of 9.1° and 15.8°, indicating the formation of the ettringite crystalline phase. Simultaneously, in the 29° to 32° range, the curve exhibits a broadened diffraction band morphology, reflecting the formation of hydrated products with amorphous or low crystallinity characteristics within the system. Based on the solid waste components of the system, it is inferred that it mainly consists of CSH and CASH gel phases. These spectral characteristics confirm the process in the formulation where calcium carbide slag dissolves hydroxide ions upon contact with water, thereby increasing the alkalinity of the liquid phase. Under this environment, the dense glassy structure of the mineral powder and fly ash on the surface is stimulated to depolymerize, and active components such as silicon and aluminum dissolve. During the set curing period, these leached substances continuously participate in the polymerization reaction, transforming into corresponding gel phase products and filling the interparticle gaps, constructing the hardened support network of the specimen at 28 days of age.
[0122] Comparative Example 1, due to the removal of industrial byproduct fluorogypsum and rapid-hardening sulfoaluminate cement, failed to exhibit the characteristic peaks of ettringite at 9.1° and 15.8°. Combined with data from Table 3, the relative intensity of these diffraction peaks decreased to 28 cps. This lack of early crystal framework weakened the physical filling effect of later hydration products, causing its 28-day compressive strength to drop to 31.4 MPa. Comparative Example 2, lacking the introduction of carbide slag, showed that the dotted line in this test group maintained only a flat baseline between 29° and 32°, resulting in the inability to extract an effective area integral in Table 3. This phenomenon reflects that the potential activity of the mineral powder in the system was not fully activated, leading to a low amount of gel phase formation in the later stages; its compressive strength and flexural strength dropped significantly to 12.5 MPa and 2.1 MPa, respectively. The correlation between the various data and the diffraction patterns indicates that carbide slag played a fundamental supporting role in establishing an alkaline activation environment and maintaining the long-term hydration process of the system.
[0123] Test Example 4:
[0124] Test steps:
[0125] 1) Prepare all materials used in Example 1. Set up Comparative Example 3, where the cementitious material, admixture, unwetted aggregate, and water are added to a mixer at once for mixing to prepare the mortar mixture of Comparative Example 3. Set up Comparative Example 4, where hydroxypropyl methylcellulose is removed from the formulation of Example 1 to prepare the mortar mixture of Comparative Example 4. The mortar mixture of Example 1 is prepared using a stepwise water addition and slurry coating process.
[0126] 2) After the mixture exits the machine, samples are taken and placed on a test substrate. The slump and flowability are measured according to the rheological performance test standard, and the flow deformation parameters in the initial stage after exiting the machine are recorded.
[0127] 3) Load each group of mortar mixtures into a 3D-printed delivery pump equipped with a pressure monitoring sensor. Set a constant discharge program and pump the mortar mixtures into the delivery hoses. This test is used to evaluate the effects of different preparation processes and water-retaining components on the outlet state and pumping throughput. Its delivery discharge rate, pipeline length, and pressure protection threshold are different from the continuous extrusion pressure monitoring condition in Test Example 1. Therefore, the pipe blockage interruption time is not directly equivalent to the pipe blockage shutdown time in Test Example 1.
[0128] 4) Observe the pumping process and record the time points from equipment startup to pipeline overload or interruption of delivery. Weigh the mass of mortar that actually passes through the delivery pipeline and is discharged from the nozzle before the interruption, and use the percentage of this mass to the total mass of the corresponding batch as the pumping throughput rate; this indicator is not converted according to the running time ratio.
[0129] 5) Extract the component consumption of the all-solid-waste cementitious material in Example 1. Set up Comparative Example 5, and use an equal mass of silicate cement to replace the all-solid-waste cementitious material components in Example 1. Input the energy consumption data of raw material acquisition, processing, grinding and transportation of each material into the life cycle assessment software to calculate the carbon dioxide equivalent per ton of cementitious material within the corresponding boundary.
[0130] Test data:
[0131] Table 4. Mortar discharge status, pumping interruption records, and carbon emission accounting data
[0132] Test object Initial slump at discharge (mm) Initial flowability at the outlet (mm) Pipe blockage interruption time (min) Pumping throughput (%) <![CDATA[Carbon emission equivalent of cementitious material (kgCO2-eq / t)]]> Example 1 185.6 162.3 - 100 45.2 Comparative Example 3 42.1 Unpredictable expansion 0.5 2.4 / Comparative Example 4 192.3 168.5 11.2 41.5 / Comparative Example 5 - - / / 856.7
[0133] Note: "-" in the table indicates that no interruption occurred during the testing period or that the rheological index test was not conducted; "No measurable extension" indicates that no related carbon emission accounting project was carried out for the test object.
[0134] Test conclusion:
[0135] Comparing the outflow rheological parameters under different preparation processes in Table 4, it can be seen that the stepwise slurry preparation and aggregate hysteresis coating process have a decisive influence on maintaining the initial workability of dry aggregate mortar. Example 1 achieved an initial slump of 185.6 mm and a stable flowability of 162.3 mm, achieving a 100% pumping throughput in the constant flow rate test. In contrast, Comparative Example 3, which used a conventional one-time water addition process, experienced a precipitous drop in initial slump to 42.1 mm, and failed to form measurable flow expansion on the test substrate. This phenomenon reveals a negative mechanism of internal moisture migration: when the total amount of mixing water directly and simultaneously contacts the unpre-wetted dry aggregate from construction waste and the powdered cementitious material, the dry aggregate, due to its high porosity, rapidly absorbs free water from the liquid phase. This disorderly water plundering caused the cementitious powder to agglomerate due to localized imbalances in the water-cement ratio, resulting in a rapid loss of fluidity in the overall mixture. Only 0.5 minutes after pumping started, the conveying process was completely interrupted due to a sharp increase in friction within the pipeline. The stepwise preparation process used in Example 1 pre-coated the surface of the dry aggregate with a high-viscosity reference slurry, physically preventing the aggregate from rapidly absorbing free water and thus successfully avoiding the risk of false coagulation during the discharge stage of the mixture.
[0136] The effect of water-retaining components in dynamic pipeline transportation environments was analyzed. Comparative Example 4, without added hydroxypropyl methylcellulose, showed similar initial rheological parameters to Example 1, but in subsequent constant-flow pumping tests, pipeline pressure overload occurred after 11.2 minutes, with an actual pumping throughput of only 41.5%. This performance reflects that initial flowability under static conditions does not necessarily represent pumping stability under dynamic compression. In the closed space of the pipeline under continuous screw pressure, the free liquid water lacking the pull of long-chain water-retaining macromolecules is compressed and forced to migrate secondary into the pores of the dry aggregate with higher water absorption, inducing severe pressure bleeding. In the later stages of material transportation, the loss of the homogeneous liquid lubricating layer caused localized dryness and blockage, ultimately leading to equipment overload and shutdown. The high-molecular-weight water-retaining component in the system of Example 1, under pressure, locked in the free water in the slurry, maintaining a homogeneous and stable flow state throughout the entire transportation cycle of the mixture.
[0137] Table 4 presents the environmental benefits of the multi-source solid waste system of this invention in terms of life cycle carbon emission accounting. Comparative Example 5 (pure silicate cement system), which replaces the cementitious material of Example 1 by the same mass, has a carbon emission equivalent as high as 856.7 kgCO2-eq / t. This high carbon emission index mainly stems from the high-temperature decomposition of carbonate minerals and the combustion of fossil fuels necessary in the traditional cement clinker preparation process. Example 1, relying on industrial solid waste (mineral powder, fly ash, fluorogypsum, etc.) to construct a cementitious network, supplemented only with a very small amount of rapid-hardening sulfoaluminate cement to regulate early strength, eliminates the carbon emission source from the high-temperature calcination stage at its source. Its core carbon footprint is limited to the early physical grinding and processing and logistics transportation of solid waste raw materials, and the final calculated carbon emission equivalent is significantly reduced to 45.2 kgCO2-eq / t. This calculation result, from a quantitative evaluation perspective, confirms the substantial engineering value of this formulation system in promoting the low-carbon substitution of bulk building 3D printing materials.
Claims
1. A solid waste-based 3D printing mortar, characterized in that, Made from the following parts by weight of raw materials: 42-60 parts of mineral powder; 15-30 parts fly ash; 16-20 parts of industrial by-product fluorogypsum; 3-10 parts of rapid-hardening sulfoaluminate cement; Alkaline activated solid waste, 2-6 parts; 80-120 parts of crushed dry aggregate from construction waste; 0.15-0.35 parts of polycarboxylate-based high-performance water-reducing agent powder; 0.005-0.03 parts of water-retaining thickener; 0.03-0.12 parts of microfiber; 18-28 parts water; The mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, and alkaline activated solid waste together constitute the cementitious material, and the total weight of the cementitious material is 100 parts.
2. The solid waste-based 3D printing mortar according to claim 1, characterized in that, The mineral powder is of grade S95, and the specific surface area of the mineral powder is 400-450 m². 2 / kg; The fly ash is Class F, Grade II fly ash; The free water content of the industrial by-product fluorogypsum is ≤1.5%.
3. The solid waste-based 3D printing mortar according to claim 2, characterized in that, The alkaline activated solid waste has a pH ≥ 12.5, and the alkaline activated solid waste is calcium carbide slag powder or steel slag powder.
4. The solid waste-based 3D printing mortar according to claim 3, characterized in that, The construction waste crushed dry aggregate is composed of waste concrete and waste bricks and tiles that have been crushed by jaw crushers and impact crushers, and then collected by screening through an iron mesh screen with a diameter of 3mm. The aggregate is then naturally air-dried until the free moisture content is ≤1.5%.
5. The solid waste-based 3D printing mortar according to claim 4, characterized in that, The water-retaining and thickening agent is hydroxypropyl methylcellulose or microbial polysaccharide sorbate.
6. The solid waste-based 3D printing mortar according to claim 5, characterized in that, The microfibers are selected from alkali-resistant glass fibers, polypropylene fibers, or basalt fibers, and the length of the microfibers is 3-6 mm.
7. The solid waste-based 3D printing mortar according to claim 6, characterized in that, The preparation method of the solid waste-based 3D printing mortar includes the following steps: Weigh out the following components by weight: mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, alkaline activated solid waste, crushed dry aggregate from construction waste, polycarboxylate-based high-performance water-reducing agent powder, water-retaining thickener, microfiber, and water. The weighed mineral powder, fly ash, industrial by-product fluorogypsum, rapid-hardening sulfoaluminate cement, alkaline activated solid waste, water-retaining thickener, and microfiber are all put into a twin-shaft forced mixer and mixed in a dry environment. A portion of the total water consumption is measured and mixed with the polycarboxylate-based high-performance water-reducing agent powder. The mixture is then added to the twin-shaft forced mixer for stirring to obtain a reference slurry phase. Keep the twin-shaft forced mixer running, pour the dry aggregate of the crushed construction waste into the reference slurry phase, and then add the remaining water. Continue stirring until the final product is obtained as a solid waste-based 3D printing mortar mixture.
8. The solid waste-based 3D printing mortar according to claim 7, characterized in that, In the step of measuring a portion of the water, the measured portion accounts for 50%-70% of the total weight of the water; In the step of adding the remaining water, the remaining water accounts for 30%-50% of the total weight of the water.
9. The solid waste-based 3D printing mortar according to claim 7, characterized in that, The mixing time under dry conditions is 11 minutes; After adding the measured amount of water and the polycarboxylate-based high-performance water-reducing agent powder, stir at low speed for 30 seconds, then switch to high-speed forced stirring for 1.5 minutes. After adding the dry aggregate from the crushed construction waste in a dry state and the remaining water, continue high-speed forced mixing for 2.5 minutes.
10. The solid waste-based 3D printing mortar according to claim 7, characterized in that, It is strictly prohibited to perform any pre-wetting or spraying treatment on the crushed dry aggregate of the construction waste.